2005
DOI: 10.1002/ijc.20943
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and subsequent colorectal cancer risk by subsite: A prospective cohort study

Abstract: In order to investigate the associations between dietary patterns and the risk of colorectal cancer by subsite in Japan, the baseline data from a population-based cohort study of 20,300 men and 21,812 women were analyzed. We conducted factor analysis and identified 3 major dietary patterns, ''healthy,'' ''traditional'' and ''Western,'' and calculated the factor scores of each pattern for individuals. During 10 years of follow-up, 370 colorectal cancer cases were identified. We found a positive association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
96
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 33 publications
13
96
1
2
Order By: Relevance
“…The first, a pattern characterized by high intakes of vegetables and fruit, and also of whole grains and white meat or fish, was frequently named as a 'prudent', 'health' or 'health conscious' pattern (16) . The other is a culturally dependent 'traditional' pattern, reflecting ethnic differences in food preferences, as reported in North America (17)(18)(19) , Europe (20)(21)(22) , Asia (23)(24)(25)(26) and Latin America (27)(28)(29)(30) . Our study has also identified one traditional pattern composed of foods that are Brazilian staple foods, such as rice and beans.…”
Section: Discussionmentioning
confidence: 99%
“…The first, a pattern characterized by high intakes of vegetables and fruit, and also of whole grains and white meat or fish, was frequently named as a 'prudent', 'health' or 'health conscious' pattern (16) . The other is a culturally dependent 'traditional' pattern, reflecting ethnic differences in food preferences, as reported in North America (17)(18)(19) , Europe (20)(21)(22) , Asia (23)(24)(25)(26) and Latin America (27)(28)(29)(30) . Our study has also identified one traditional pattern composed of foods that are Brazilian staple foods, such as rice and beans.…”
Section: Discussionmentioning
confidence: 99%
“…8,[27][28][29][30][31] Most of the prospective and case-control studies reported significant increases in risk of colorectal cancer associated with the Western pattern. 8,27,[29][30][31] Although the precise definition of the Western pattern is difficult to establish, red meat, processed meat and eggs are consistently present in this pattern. According to Kesse et al 31 the drinker pattern was directly associated with colorectal cancer, replicating current evidence which strongly suggests that alcohol drinking is a risk factor for colon cancer, mainly among men.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining derived dietary patterns and cancer end points have, until recently, been rarer, but a number of recent studies have shown associations between dietary patterns and oral and pharyngeal (de Stefani et al 2005), prostate (Walker et al 2005), colorectal (Kim et al 2005) and lung cancers (Balder et al 2005), but no association between dietary patterns and breast (Fung et al 2005) and pancreatic cancers (Michaud et al 2005).…”
Section: Dietary Patterns and Diseasementioning
confidence: 99%